VISUAL ANALYSIS OF BUILDING DAMAGE LEVEL AT SEBELAS MARET UNIVERSITY DORMITORY - Anton Aminanto; Ary Setyawan; Dewi Handayani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The structural integrity of a building is a primary parameter in ensuring the safety and security of its occupants. Over time, structural and non-structural performance tends to degrade due to building age, environmental factors, and usage intensity. This study aims to analyze the physical damage level of Building E at the Sebelas Maret University (UNS) Student Dormitory to provide a technical basis for building maintenance and repair management. The research methodology involved a technical evaluation through visual inspection of both structural and non-structural elements. The analysis results indicate that within the structural elements, the highest damage percentage was found in beams at 20.43%, followed by columns at 0.16%, while stair elements showed no damage. Regarding non-structural elements, the dominant damage occurred in wall finishing/paint at 6.86%, followed by ceilings at 1.96%, and window components at 0.5%. Other elements, including light brick walls, doors, and floor coverings, remained in good condition with no identified damage. The cumulative calculation shows that the total damage percentage for Building E of the UNS Student Dormitory is 3.28%. Based on building damage classifications, this value falls well below the 30% threshold, categorizing the building as having light damage. As a follow-up measure, optimization of periodic preventive maintenance management is required to prevent further degradation and ensure the long-term functional sustainability of the building.